2020
DOI: 10.3390/rs12233880
|View full text |Cite
|
Sign up to set email alerts
|

An Accurate Vegetation and Non-Vegetation Differentiation Approach Based on Land Cover Classification

Abstract: Accurate vegetation detection is important for many applications, such as crop yield estimation, land cover land use monitoring, urban growth monitoring, drought monitoring, etc. Popular conventional approaches to vegetation detection incorporate the normalized difference vegetation index (NDVI), which uses the red and near infrared (NIR) bands, and enhanced vegetation index (EVI), which uses red, NIR, and the blue bands. Although NDVI and EVI are efficient, their accuracies still have room for further improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…Comparisons of mining area classification results based on spectral information with integrated digital elevation model (DEM) and spectral information data reveal superior results from the latter [ 20 ]. Machine-learning algorithms (MLAs) accommodate varied feature sets, with algorithms, such as the support vector machine (SVM) [ 21 , 22 , 23 , 24 ] and random forest (RF) [ 22 ], widely employed for LULC classification in complex mining areas [ 18 , 25 , 26 , 27 , 28 ]. Chen et al [ 29 ] highlighted the importance of obtaining remote sensing features and developing an effective classification model for fine LULC classification.…”
Section: Introductionmentioning
confidence: 99%
“…Comparisons of mining area classification results based on spectral information with integrated digital elevation model (DEM) and spectral information data reveal superior results from the latter [ 20 ]. Machine-learning algorithms (MLAs) accommodate varied feature sets, with algorithms, such as the support vector machine (SVM) [ 21 , 22 , 23 , 24 ] and random forest (RF) [ 22 ], widely employed for LULC classification in complex mining areas [ 18 , 25 , 26 , 27 , 28 ]. Chen et al [ 29 ] highlighted the importance of obtaining remote sensing features and developing an effective classification model for fine LULC classification.…”
Section: Introductionmentioning
confidence: 99%
“…Pixel-based and object-based methods can be used in land cover classification. Kwan et al [29] observed that red-green-blue (RGB) and near infrared (NIR) bands can perform better than the NDVI and EVI approaches in vegetation detection based on land cover classification. For land cover classification, Kwan et al [30] used a limited number of bands (RGB + NIR and RGB + NIR + LiDAR) and EMAP-based augmentation; moreover, they gave a comprehensive performance evaluation of two CNN-based deep learning (customized CNN and CNN-3D) algorithms.…”
Section: Introductionmentioning
confidence: 99%
“…Multi-scale covariance maps were introduced to solve the overfitting problem of convolutional neural networkbased methods in HSI classification [26]. Additionally, the existing works show that in the classification process, the combination of spatial information with dimensionality reduction [27], sparse representation [28,29], low rank representation [30], convolutional neural network [31] and various techniques do contribute to improving the classification accuracy.…”
Section: Introductionmentioning
confidence: 99%